Emissions impacts of future battery storage deployment on regional power systems - Bistline, John E.T.; Young, David T. (Applied energy, 2020)
[Display omitted] •We examine the emissions impact of battery storage across sensitivities and regions.•Existing studies focus on dispatch; we show how investment effects drive emissions.•Emissions impacts of storage vary based on policy and market assumptions.•Storage emissions reductions are more likely when wind and solar are lower cost. Battery storage technologies have attracted attention from policymakers for their potential to reduce electric sector emissions by enabling greater wind and solar penetration. Yet existing studies indicate that adding energy storage actually increases emissions. The difference may be explained by the absence in the previous literature of “investment effects” – changes in deployment of other generation technologies after storage is deployed. Our paper tests this hypothesis by evaluating battery-storage-induced emissions changes using a model that accounts for both long-run investment and dispatch effects simultaneously across regions in the United States, which can be used to separate the relative magnitudes of these two effects. Model results indicate that the investment effect dominates the dispatch effect under a range of sensitivities. We find that emissions may increase or decrease with battery storage, depending on policy and market assumptions, with reductions more likely in environments where wind and solar are more economically competitive relative to natural-gas-fired generation. These results suggest that existing studies that only account for operational impacts likely underestimate potential emissions changes from battery storage deployment.